Effective use of micro-silica extracted from rice husk ash for the production of high-performance and sustainable cement mortar. (20th October 2020) - Khan, Kaffayatullah; Ullah, Muhammad Fahad; Shahzada, Khan; Amin, Muhammad Nasir; Bibi, Tayyaba; Wahab, Nauman; Aljaafari, Abdullah
Highlights: Micro silica extracted from RHA (EMS) possessed very high fineness and reactivity. Addition of EMS increases strength and decreases porosity of the mortar samples. Incorporation of EMS to mortar bar samples showed better resistance to ASR. EMS improved both micro and pore structure due to its high fineness and reactivity. Abstract: Utilization of high-performance and highly reactive sustainable materials in concrete are gaining popularity nowadays for the development of strong, durable and sustainable infrastructures. Therefore, current study focuses on viable use of highly reactive silica extracted from rice husk ash (RHA) for the production of high-performance sustainable cement mortar. Mortar containing various percentages of extracted micro-silica (EMS) as a partial substitute of cement (5%, 15%, and 25%) were cast to test fresh as well as hardened properties, and compare its results to that of control mortar. Test results showed that the standard consistency increased with increasing percentage of EMS, whereas, a delay in the setting time was observed. The compressive and flexural strengths of all mortar mixes containing EMS were improved with aging and an effective role played by EMS in mitigating the expansion caused by the alkali–silica reaction was observed. However, a slight reduction of strength at later ages was observed in mortar having 25% EMS. At relatively low addition of EMS (5% and 15%), micro- and pore structural investigations revealed the formation of improved high-density C-S-H phases, which aid the formation of refined and homogenous microstructures. The agglomeration was observed through micro- and pore structural investigations in high dosage EMS mortars that occurred due to the oversaturation and poor dispersion, which consequently affected the hydration products and increased the porosity of the paste matrix. The current findings suggest that the reactive silica resource extracted from RHA can be used as a potential revenue stream in concrete industry for the development of high-performance and sustainable cement mortar.